I am trying to simplify this equation: ( ' = NOT)


The result I get is when using demorgan's and other rules is:


However, I know that this answer is only partially complete since I know from using a karnaugh map that the correct answer is


I know that the law of common identities states that

A'B + B = A+B

and this makes sense to me, but I'm not sure how I can apply that law here. If common identities is not the way to go, could someone show me how to solve this problem?


From the context, I suppose you're using $'$ as a prefix notation, as it is usual for $\neg$.
Note however that $'$ is normally used as a postfix notation, so as $A'$ with the same meaning as $\neg A$.

That said, you're claiming (with the usual notation) that using a Karnaugh map, you proved that $$A'D+ACD+AB'C+ABCD = D+AB'C.$$ But you must have got wrong somewhere, since applying with $A=D=1$ and $C=0$ (whatever $B$), this gives $0=1$.

By the way, you can get the other result using the identity that you mention like this: \begin{align} A'D+ACD+AB'C+ABCD &= A'D+ACD+AB'C\\ &= (A'+AC)D+AB'C\\ &= (A'+C)D +AB'C\\ &= A'D + CD + AB'C, \end{align} where the first equality follows from $ACD+ABCD=ACD$, the second and the fourth are distributivity and the third is the law you stated.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.